Value chain in the relationship of intellectual capital and firm's performance - Harry Suharman; Dini Wahjoe Hapsari; Nurul Hidayah; Rr. Sri Saraswati (Cogent Business & Management, 2023)
State-Owned Enterprises (SOEs) are companies whose majority shares are owned by the government. The prime focus of this paper, determine the impact of intellectual capital in State-Owned Enterprises (SOEs) on firm performance using the value chain as a mediating variable. This research methodology begins with selecting of respondents; respondents in this study were 207 general managers and directors from 69 Indonesian State-Owned Enterprises. The data used in this study's analysis came from questionnaires filled out by respondents. Structural Equation Modelling is a tool for data analysis. The study's key findings are statistical tests that show intellectual capital directly impact the value chain and firm performance. Research contribution to raise awareness of intellectual capital, relationships, and the value chain among stakeholders in state-owned enterprises. This finding indicates that SOEs have improved the value chain and firm performance through useful resource management. Furthermore, through mandatory company regulations, this study contributes formulating company policies, particularly internal performance regulations.
Keywords: M41; 650; firm performance; intellectual capital; managerial firms; value chain